KETERKAITAN PROSES MANAJEMEN PENGETAHUAN DENGAN KINERJA KERJA YANG DIMEDIASI OLEH KINERJA MANAJEMEN PENGETAHUAN: BUKTI EMPIRIS PADA PERUSAHAAN PENYALUR TENAGA KERJA INDONESIA (TKI) - Netania Emilisa; Pandu Andi Wiguna; Advendi Simangunsong (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study aims to identify and measure the influence of knowledge management process on job performance mediated by knowledge management performance. The number of non managerial employees amounted 112 people as respondents. The method to collecting the data uses census by distributing questionnaires to all respondents. The design of the study is hypothesis testing with structural equation modeling (SEM) as a tool of analysis. The findings are that the knowledge management process has a positive influence on knowledge management performance, knowledge management performance has a positive influence on job performance, knowledge management process has positive effect on job performance, and knowledge management process has positive effect on job performance mediated by knowledge management performance. Managerial implications are the departments in which employees work should appreciate employees who provide new ideas and knowledge to the company. In addition, the management should provide an opportunity for employees to share knowledge with other employees and solve existing problems.